ANALISIS PERLINDUNGAN HUKUM DALAM KESEPAKATAN INVESTASI ANTARA INVESTOR DAN UMKM PADA PT. INTEGRITECH JASA MANDIRI KECAMATAN PARINDU - NIM. A1012181124, MICHAEL ONO BUTUOH (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract Legal protection for MSMEs in partnerships with investors has actually been guaranteed in Law Number 20 of 2008 concerning Micro, Small, and Medium Enterprises. There are several important articles that explicitly regulate the principles of justice, transparency, and balance of rights and obligations in partnerships between MSMEs and external parties, including investors. Article 21 of Law Number 20 of 2008 states that in establishing partnerships, large business actors and MSMEs must base themselves on the principles of togetherness, mutual strengthening and benefit, trust, transparency, proportional sharing of benefits and risks, efficiency, justice, and sustainability. The principle of proportional sharing of benefits and risks is very important because it is the main benchmark for assessing whether an investment relationship is exploitative or fair for both parties. Furthermore, Article 26 of the Law provides a guarantee of legal protection for MSMEs against unhealthy business practices, such as the existence of unilateral clauses in contracts, disproportionate control of resources by more dominant business partners, and other forms of exploitation. Thus, the law has normatively protected MSMEs from unfair partnership practices. This research is a normative legal research. Normative legal research is a research that only processes and uses secondary data related to the problem of